Perencanaan Ulang Jembatan Jetak Bojonegoro Menggunakan Struktur PCI – Girder dan Penerapan Building Information Modelling (BIM) 5D - Ivory Quthub Manar; Siti Husnul Hotimah; Asri Nurdiana; Bambang Setiabudi (Civil Infrastructure Engineering and Architectural Design, 2026)
The Jetak Bridge in Bojonegoro, originally a Steel Box Girder type, was redesigned using a Precast Concrete I-Girder (PCI-Girder) system to improve safety and serviceability. The new design applies BIM 5D for integrated analysis, covering structural calculation, 3D modelling, scheduling, and cost estimation. Structural planning refers to SNI 1725:2016 and related standards. The redesigned bridge has a 50 m span and 19.3 m width, supported by PCI-Girders and pile foundations. Analysis results confirm that the structure meets strength, stability, and serviceability requirements. The BIM 5D workflow produced reliable outputs for quantity take-off, cost, and project duration. The estimated construction cost is IDR 30.36 billion with a duration of 40 weeks. This study highlights that BIM 5D enhances accuracy, transparency, and efficiency in bridge planning and implementation.